Discoveries of Vilnius’ Urbanism - Janušauskaitė, Viltė (Lietuvos istorijos studijos, 2017)
About the thesis of Karolis Kučiauskas “The urban concept of prewar Vilnius and its reception during World War II and the postwar years (1932–1956)”